Glycosaminoglycan binding by Borrelia burgdorferi adhesin BBK32 specifically and uniquely promotes joint colonization. (24th January 2015) - Lin, Yi‐Pin; Chen, Qiang; Ritchie, Jennifer A.; Dufour, Nicholas P.; Fischer, Joshua R.; Coburn, Jenifer; Leong, John M.
Summary Microbial pathogens that colonize multiple tissues commonly produce adhesive surface proteins that mediate attachment to cells and/or extracellular matrix in target organs. Many of these 'adhesins' bind to multiple ligands, complicating efforts to understand the role of each ligand‐binding activity. Borrelia burgdorferi, the causative agent of Lyme disease, produces BBK32, first identified as a fibronectin‐binding adhesin that promotes skin and joint colonization. BBK32 also binds to glycosaminoglycan (GAG), which, like fibronectin is ubiquitously present on cell surfaces. To determine which binding activity is relevant for BBK32‐promoted infectivity, we generated a panel of BBK32 truncation and internal deletion mutants, and identified variants specifically defective for binding to either fibronectin or GAG. These variants promoted bacterial attachment to different mammalian cell types in vitro, suggesting that fibronectin and GAG binding may play distinct roles during infection. Intravenous inoculation of mice with a high‐passage non‐infectious B. burgdorferi strain that produced wild‐type BBK32 or BBK32 mutants defective for GAG or fibronectin binding, revealed that only GAG‐binding activity was required for significant localization to joints at 60 min post‐infection. An otherwise infectious B. burgdorferi strain producing BBK32 specifically deficient in fibronectin binding was fully capable of both skin and joint colonization in the murine model, whereas a strain producing BBK32 selectively attenuated for GAG binding colonized the inoculation site but not knee or tibiotarsus joints. Thus, the BBK32 fibronectin‐ and GAG‐binding activities are separable in vivo, and BBK32‐mediated GAG binding, but not fibronectin binding, contributes to joint colonization.